A Systematic DFT Approach for Studying Mechanisms of Redox Active Enzymes - Siegbahn, Per E. M.; Blomberg, Margareta R. A. (Frontiers in Chemistry, 2018)
When DFT has been applied to study mechanisms of redox processes a common procedure has been to study the results for many different functionals. For redox reactions involving the first row transition metals, this approach has given very different results for different functionals. The conclusion has been that DFT cannot be used for these reactions. In the meantime, results with strong predictability have been generated, most noteworthy for photosystem II, where all DFT predictions have been verified by experiments performed later. In order to obtain these predictive results using DFT, an alternative, systematic approach has been used, where the key differences between the results for different functionals can be rationalized by using a single parameter, rather than using the very large number of differences in the functionals.